The Relationship Between Tahajud Prayer and Anxiety Levels Among the Elderly in Darmorejo Village, Madiun Regency - Rezi Febriani Nuryanto; Noor Yazid; Rochman Basuki; Muslimah (International Journal of Health and Pharmaceutical (IJHP), 2026)
The Relationship of Tahajud Prayer with the Level of Anxiety in the Elderly in Darmorejo Village, Madiun Regency. Anxiety is a state of excessive tension that can be characterized by feelings of worry that arise because there is a response to stressful conditions, such as sweating, racing heart and difficulty breathing. In Indonesia, anxiety is very high for ages 55-65 years, the prevalence of anxiety scores 6.9%, while 9.7% are at the age of 65-75 and 13.4% are aged 75 years and over. In Islam there is a way to deal with anxiety, namely by means of a religious approach, one of the religious approaches that can be done is the tahajud prayer. Therefore, the purpose of the researchers conducting this study was to analyze the relationship between tahajud prayer and the level of anxiety in the elderly in Darmorejo village, Madiun regency. This study used a cross sectional quantitative design. The sample to be studied is the elderly in Darmorejo Village, Madiun Regency who meet the inclusion and inclusion criteria. The technique for taking samples is carried out by total sampling. Data collection techniques include filling out tahajud prayer questionnaires and Zung Self Anxiety Rating Scale. Data analysis for hypothesis testing using Rank spearman. The results of the study There is a significant relationship because the value of p < 0.05 with the results of the.